2020
DOI: 10.3390/ma13225058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Tempering Behavior of Different Martensitic Steels by Means of In-Situ Diffractometry and Dilatometry

Abstract: Martensitic steels are tempered to increase the toughness of the metastable martensite, which is brittle in the as-quenched state, and to achieve a more stable microstructure. During the tempering of steels, several particular overlapping effects can arise. Classical dilatometric investigations can only detect effects by monitoring the integral length change of the sample. Additional in-situ diffractometry allowed a differentiation of the individual effects such as transformation of retained austenite and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…However, the precipitation started after 1300 s. An opposite trend was observed at 200 °C in 5Mn steel. In this case, the RCL increased from 0.138% to 0.153% after 450 s. This observation confirmed that some amount of carbides were formed in RA or thermal decomposition of RA into ferrite and carbides took place [33]. Such effect was not noted for the alloy containing 3% of manganese.…”
Section: Thermal Stability Of Retained Austenite At Elevated Temperaturessupporting
confidence: 71%
“…However, the precipitation started after 1300 s. An opposite trend was observed at 200 °C in 5Mn steel. In this case, the RCL increased from 0.138% to 0.153% after 450 s. This observation confirmed that some amount of carbides were formed in RA or thermal decomposition of RA into ferrite and carbides took place [33]. Such effect was not noted for the alloy containing 3% of manganese.…”
Section: Thermal Stability Of Retained Austenite At Elevated Temperaturessupporting
confidence: 71%
“…From Figure 6 b,d, the microstructure, after quenching and tempering, is formed of tempered martensite and carbide. Thus, austenitizing at 1040 °C for 30 min and then quenching in oil can ensure that the austenite is mainly transformed into lath martensite, but this is not sufficient to completely dissolve the carbides [ 28 , 37 , 38 ]. Moreover, the distribution of Nb(C,N) in Figure 6 a is not uniform, in comparison with the microstructure seen after the quenching and tempering processes in Figure 6 b.…”
Section: Resultsmentioning
confidence: 99%
“…As the as-quenched martensite transitions to tempered martensite, there is precipitation of secondary carbides. Precipitation of carbides lowers the amount of alloy elements dissolved into the matrix, which ultimately reduces stored energy (strain) in the lattice of the Fe-matrix [22,24].…”
Section: °C Temperingmentioning
confidence: 99%